O museu na era virtual: uma análise sobre os processos comunicativos on-line do Museu da UFPA - SOUZA, Lucimery Ribeiro de (Universidade Federal do Pará, 2018)
The objective is to analyze how the museological institution interacts through on-line social networks with its public and how the responsible agents understand this communication process taking into account the social function of museums and the need to promote dialogue with society. To accomplish this reflection, it investigates the Museum of the Federal University of Pará (MUFPA), situated in Belém (PA). As theoretical foundation, it is used the reflections made from literature relating to the Communication (BRAGA; FRANÇA; MARTINO; RECUERO) and the Museology field (CARVALHO; CURY; GUARNIERI; MUCHACHO; SCHEINER). As methodological procedures for data collection, two main techniques are highlighted: the direct observation unsystematic and systematic of social networks Facebook and Instagram appropriated by the Museum of UFPA and interviews from semi-structured scripts with the subjects involved in the production and circulation of the content published in the virtual environments connected to MUFPA. It concludes that the way MUFPA makes use of the studied on-line environments provides expansion and strengthening of the local social ties established virtually, through the practice of posts whose contents portray regional aspects and scenes of the day-by-day of the museum. The maintenance of this practice may provide that the links established in cyberspace are scaled to the physical space of the museum, with potential to reframe the dynamics of presential visitation of the museum circuit in the city of Belém. Analyze the museum as an object allows an extension of the perspectives of Communication and Museology area, and points the necessity for further research that investigate more broadly the museological institutions as a medium, for example, the communication in the experience of the visit to the museum, the dynamic and the museums and its diferente public, among other possibilities.